Synergy of Sharīʿah Fintech Regulation and Halal Tourism: Towards a Sustainable Economy Based on Islamic Law - Zainuddin; Wirdyaningsih Wirdyaningsih; Iffah Karimah; Fahrul Fauzi; Aufi Qonitatus Syahida; Zalina Zakaria (Sriwijaya Law Review, 2026)
The synergy between Sharīʿah fintech regulation and halal tourism must be grounded in the objectives of Islamic law (maqāṣid al-sharīʿah), which prohibit usury (ribā), uncertainty (gharār), and gambling (maysir), to foster a fair, transparent, and sustainable economic ecosystem that empowers local communities. In practice, however, this synergy faces several challenges, including regulatory oversight gaps, superficial Sharīʿah compliance, cross-sectoral regulatory fragmentation, low levels of Sharīʿah financial literacy, and limited digital infrastructure. In Indonesia, Sharīʿah fintech is regulated by POJK No. 77/2016 on technology-based lending services, DSN-MUI Fatwa No. 117/2018 on Sharīʿah-compliant fintech operations, and PBI No. 19/2017 concerning fintech implementation and financial system stability. Halal tourism, meanwhile, is governed by Law No. 33/2014 on Halal Product Assurance, which mandates halal certification for goods and services, including tourism-related activities. This normative legal research employs legislative, conceptual, and analytical approaches, drawing on primary and secondary legal materials obtained through literature review and document analysis. The findings indicate that regulatory integration between Sharīʿah fintech and halal tourism is essential for promoting sustainable and inclusive economic growth. Such synergy enhances transparency, accountability, and trust, while enabling halal tourism operators to access ethical financing through instruments such as muḍārabah and mushārakah. Ultimately, this collaboration strengthens Indonesia’s national halal ecosystem, supports SMEs, enhances economic development, and increases global competitiveness in halal market.